Flowers : more than 50 projects and techniques for drawing, painting, and creating your favorite flowers and botanicals in oil, acrylic, pencil, and more!.: more than 50 projects and techniques for drawing, painting, and creating your favorite flowers and botanicals in oil, acrylic, pencil, and more!. (2017) - Unknown
No abstract available